2012
DOI: 10.1074/jbc.m111.297192
|View full text |Cite
|
Sign up to set email alerts
|

Solute Carrier Family 26 Member a2 (Slc26a2) Protein Functions as an Electroneutral SO42−/OH−/Cl− Exchanger Regulated by Extracellular Cl−

Abstract: Background: Slc26a2 is an SO 4 2Ϫ transporter, mutations in which cause diastrophic dysplasia. How Slc26a2 transports SO 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 56 publications
4
52
0
Order By: Relevance
“…On the other hand, slc26a6 and NaDC-1 can be readily co-immunoprecipitated (see Figure 2D and discussion below). Finally, inhibition of NaDC-1 was not restricted to slc26a6 because the 2Cl -/1HCO 3 2 exchanger slc26a3 6,7 similarly inhibited NaDC-1 activity ( Figure 2B), although the SO 4 22 /OH 2 /Cl 2 exchanger slc26a2 23 did not (Supplemental Figure 3). …”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, slc26a6 and NaDC-1 can be readily co-immunoprecipitated (see Figure 2D and discussion below). Finally, inhibition of NaDC-1 was not restricted to slc26a6 because the 2Cl -/1HCO 3 2 exchanger slc26a3 6,7 similarly inhibited NaDC-1 activity ( Figure 2B), although the SO 4 22 /OH 2 /Cl 2 exchanger slc26a2 23 did not (Supplemental Figure 3). …”
Section: Resultsmentioning
confidence: 97%
“…Mutations within this motif altered Cl − transport and coupling in ClCs (34,35). Recently, we reported that regulation of slc26a2 by extracellular Cl − is altered by mutations in slc26a2 GXXXP motif (36). NBCe1-B has three GXXXP motifs in the N terminus (Fig.…”
Section: Imentioning
confidence: 97%
“…The present study has uncovered a previously unidentified function of Cl − in as a signaling ion that regulates the activity of other transporters, including transporters that do not transport Cl − , such as the NBCs. The regulation seems to be mediated by sites containing GXXXP motifs, which have been associated with Cl − sensing and transport in other transporters (32)(33)(34)(35)(36). In the ClC channels, residues in the GXXXP motifs from several regions are brought together to form the Cl − binding sites (32).…”
Section: CLmentioning
confidence: 99%
“…Previous studies of N-glycan sites have focused on a few members of the SLC26 family. SLC26A2 (DTDST) expressed in HEK cells showed two bands of 120 and 80 kDa with the upper band predominating (24,37), as did the protein in isolated rat proximal tubule microvillus membrane vesicles (9). Previous N-glycosylation studies of SLC26A3 identified N-glycosylation sites at closely spaced positions Asn153, 161, and 165, showing that this loop region is extracellular (20).…”
mentioning
confidence: 89%
“…For a recent review on SLC26 family members, see also Alper and Sharma (1). SLC26A1 and A2 transport sulfate, oxalate, and glyoxalate in an exchange mode with chloride (6,19,37,45,49,50,68). SLC26A1 (Sat-1) is located in the basolateral membrane of hepatocytes, enterocytes, and proximal tubular epithelial cells, while SLC26A2 (DTDST) is found in chrondrocytes and in the apical membrane of colonic epithelial cells and renal proximal cells.…”
mentioning
confidence: 99%